Outcomes of arthroscopic repair using the all-inside inter-leaf vertical suture technique for horizontal meniscal tears sustained in sports. Issue 41 (9th October 2020) - Atsumi, Satoru; Hara, Kunio; Arai, Yuji; Kamitani, Aguri; Nakagawa, Shuji; Inoue, Hiroaki; Kubo, Toshikazu
Abstract : Abstract: The aim of the study was to evaluate the outcomes of arthroscopic repair using the all-inside inter-leaf vertical suture arthroscopic technique for sports-related horizontal meniscal tears. The inter-leaf vertical suture procedure was performed to repair sports-related horizontal tears in the middle and posterior segments of the medial (11 cases) and lateral (2 cases) menisci in 13 patients (mean age: 30 ± 14 years). Pre- and post-operative Barrett criteria, Lysholm scores, and patient ability to resume sports were assessed. Magnetic resonance imaging (MRI) grades and signal intensity changes near the joint capsule were evaluated in the 9 cases among which pre- and post-operative MRI images were available. All Barrett criteria items were negative following surgery; Lysholm scores increased from 70.2 ± 13.1 before surgery to 98.9 ± 2.64 after surgery ( P  < .01). All patients were able to resume their sport. Preoperative MRI grade of tears was 3 for all patients; postoperative MRI grades were 1 in 3 cases, 2 in 4 cases, and 3 in 2 cases ( P  < .05). Importantly, MRI signal intensity at the repaired menisci near the joint capsule was reduced in 8 of these 9 cases postoperatively. The inter-leaf vertical suture procedure is associated with good outcomes for horizontal tears in the middle and posterior segments of the medial and lateral menisci. The procedure is useful and convenient.